PENGARUH MOTIVASI BELAJAR, GAYA BELAJAR DAN KECERDASAN SPIRITUAL PESERTA DIDIK TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM KELAS XI SMA NEGERI 1 TALAWI KABUPATEN BATU BARA TAHUN PELAJARAN 2017/2018 - Rafika Ulfa, Ali Imran Sinaga, Indra Jaya (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
Abstract: The students’ learning echievement in education of Islamic study are influenced by somefactors, namely internal and external factors. The internal factors that can influence learning echievementare learning motivation, learning style, and spiritual intelegence. The research aims to discover the influenceof learning motivation, learning style, and spiritual intelegence with Education of Islamic Study learningechievement of the students at SMA Negeri 1 Talawi in Batu Bara.The research is ex post facto. Thepopulation of the research were the students of class XI at SMA Negeri 1 Talawi in academic year 2017/2018. The samples were 70 students taken by using stratified random sampling technique. Data werecollected by employing questionnaire. The technique of analysis data include instrument test, validity andreliability; test prerequisites research, consisting of normality, linearity and homogenity test; the hypothesistest, used analysis simple regression and analysis multi regression of three predictors. The result of thisresearch were (1) There are positive and significant the effect of learning motivation on learning achievementeducation of islamic studies with the influence of power is 0,289 or 28,9%. (2) There are positive andsignificant the effect of learning style on learning achievement education of islamic studies with the influenceof power is 0,486 or 48,6%. (3) There are positive and significant the effect of spiritual intelligence onlearning achievement education of islamic studies with the influence of power is 0,486 or 48,6%. (4) Thereare positive and significant the effect of learning motivation, learning style, and spiritual intelligence onlearning achievement education of islamic studies with the influence of power is 0,314 or 31,4%. Therefor,the influence of learning achievement based on condition before is determined by learning motivation,learning style, and spiritual intelligence.Key Words:Learning Echievement, Learning Motivation, Learning Style, Spiritual Intelegence